The Finnish Team Academy model: Implications for management education. Issue 2 (April 2015) - Tosey, Paul; Dhaliwal, Spinder; Hassinen, Jukka
This article explores an innovative model of management education, the Team Academy based in Finland, in which teams of learners create and operate real enterprises, supported by coaches. The contributions of the article are to provide insights into how the Team Academy works, and to review its implications for theories of management learning and educational design. Based on a case study of the Team Academy model, we argue that management education programmes need to be construed as artificially created learning environments, and specifically as 'micro-cultures' – local contexts in which pedagogical and cultural practices coalesce. The concept of a micro-culture can bring together four main attributes of learning environments, namely, social embeddedness, real-worldness, identity formation, and normative. Construing learning environments in this way has likely important implications for the theory and practice of management learning and education, since a micro-culture is a complex, emergent phenomenon that is not necessarily controllable or transferable.